Lack of impact of protease inhibitor resistance-associated mutations on the outcome of HIV-1-infected patients switching to darunavir-based dual therapy. Issue 3 (3rd March 2020) - Vizcarra, Pilar; Blanco, José L.; Montejano, Rocío; Negredo, Eugenia; Espinosa, Nuria; Casado, José L.; ,
Abstract: Background: Little is known about the impact of baseline resistance-associated mutations (RAMs) on the outcomes of alternative therapeutic strategies such as dual regimens. We assessed the efficacy of boosted darunavir plus raltegravir (DRV + RAL) dual regimen as a simplification strategy in virologically suppressed patients with protease inhibitors RAMs. Methods: Retrospective, multicentre study on the evolution of 228 heavily pretreated patients who switched to boosted DRV + RAL according to genotypic sensitivity score (GSS). Patients were classified as full susceptible (GSS = 2; n  = 177), or with reduced darunavir susceptibility (GSS < 2; n  = 51). Results: Median (range) number of prior antiretroviral regimens was 9 (6–14), with a median (range) of 2 (1–3), 4 (3–6), and 5 (2–9) major mutations to non-nucleoside reverse transcriptase inhibitors, nucleoside reverse transcriptase inhibitors, and protease inhibitors, respectively. The median time of virological suppression before simplification was 49 months (IQR 39.8–63.5). Patients with reduced darunavir GSS showed a higher number of protease inhibitors-RAMs (9.3 vs 4.5, p  < .01) and were suppressed for longer time (median, 61 months). At week 96, the rate of virological failure was low (two cases, 0.9%; 95% confidence interval, CI, 0.4–2.7%), and the efficacy, excluding non-virological reasons, was 96.8% (95%CI, 90.2–98.4%), without differences according to GSS or protease inhibitors-RAMs. Furthermore, significant improvements in CD4+ counts and CD4/CD8 ratio were observed ( p  < .01) in both groups. Conclusions: Treatment simplification to a dual regimen of boosted DRV + RAL after long-term virological suppression was not associated with a high risk of treatment failure, even in patients harbouring protease inhibitors-resistant HIV infection.